Correction: Measured and simulated thermoelectric properties of FeAs2−xSex (x = 0.30–1.0): from marcasite to arsenopyrite structure. Issue 9 (26th April 2021) - Perez, Christopher J.; Devlin, Kasey P.; Skaggs, Callista M.; Tan, Xiaoyan; Frank, Corey E.; Badger, Jackson R.; Kang, Chang-Jong; Emge, Thomas J.; Kauzlarich, Susan M.; Taufour, Valentin; Kotliar, Gabriel; Lapidus, Saul H.; et al.
Abstract : Correction for 'Measured and simulated thermoelectric properties of FeAs2− x Se x ( x = 0.30–1.0): from marcasite to arsenopyrite structure' by Christopher J. Perez et al., Mater. Adv., 2020, 1, 1390–1398, DOI: ; 10.1039/D0MA00371A .